Tourism Village Development Strategy for a Sustainable Tourism Destination: the Case of Tajen Village, Tabanan-Bali - Endrayani; Yuda, Ida Bagus Nyoman Krisna Prawira; Putri, Ida Ayu Karina (Bali Journal of Hospitality, Tourism and Culture Research, 2025)
Tajen Village is one of the pioneering tourism villages in Tabanan Regency that has natural, cultural, and artificial tourism potential, so it is very appropriate to be developed. This research aims to find out how internal and external conditions are, as well as to find out strategies that can be proposed in the development of Tajen Tourism Village as environmentally friendly tourism in Tabanan Regency. The data collection technique in this study is through observation, in-depth interviews, documentation, and literature studies. This study uses the concept of AFITH (Attraction, Facilities, Infrastructure, Transportation, and Hospitality) and PEST (Political, Economic, Social, and Technological) analysis. The informant determination technique in this study uses purposive sampling techniques. The informants selected in this study were key informants, main informants and additional informants. The results of the study show that there are four strategic points in the development of Tourism Villages, namely: strategies for developing tourist attractions and tourism destinations, comprehensive strategies for tourism programs, strategies for improving quality, and strategies for human resource development.